Respuesta :
The equation to be solved is: 3 [ 2 ^ (2t - 5) ] - 4 = 10
The steps are:
1) transpose - 4=> 3 [ 2^ (2t - 5) ] = 10 + 4
2) Combine like terms => 3 [2^ (2t - 5) ] = 14
3) Divide both terms by 3 => 2^ (2t - 5) = 14 / 3
4) Take logarithms of both sides => (2t - 5) log (2) = log (14/3)
5) Divide both sides by log (2) =>
log (14/3)
2t - 5 = -------------------
log (2)
6) transpose - 5+>
log (14/3)
2t = ------------------- + 5 = 2.22 + 5
log (2)
2t = 7.22
7) divide both sides by 2 => t = 7.22 / 2 = 3.61
The steps are:
1) transpose - 4=> 3 [ 2^ (2t - 5) ] = 10 + 4
2) Combine like terms => 3 [2^ (2t - 5) ] = 14
3) Divide both terms by 3 => 2^ (2t - 5) = 14 / 3
4) Take logarithms of both sides => (2t - 5) log (2) = log (14/3)
5) Divide both sides by log (2) =>
log (14/3)
2t - 5 = -------------------
log (2)
6) transpose - 5+>
log (14/3)
2t = ------------------- + 5 = 2.22 + 5
log (2)
2t = 7.22
7) divide both sides by 2 => t = 7.22 / 2 = 3.61
Answer:
Below
Step-by-step explanation:
The equation: 3(2^2t-5)-4=10
1) Add 4 to each side of the equation --> 3(2^2t-5)=14
2) Divide both sides of equation by 3 --> (2^2t-5)=14/3
3) Take the log of each side --> log(2^2t-5)=log(14/3)
4) Use the Exponential Property and write 14/3 in decimal form --> (2t-5)log2=log4.67
5) Divide each side by log 2 --> 2t-5 = log4.67/log2
6) Find the value of log4.67/log2 and substitute --> 2t-5=2.23
7) Add 5 to each side of the equation --> 2t=2.23+5
8) Simplify --> t=3.625
Sorry, no explanations.